Problems faced by the secondary schools ofSandilipay division in teaching and learning of home economics. - Mayoorathy, T.; Pathmasany, K.; Nithlavarnan, A. (South Eastern University of Sri Lanka, University Park, Oluvil, Sri Lanka, 2019)
The Home Economic subject is given a special important place amongst subjects that empower students for their livelihood. It has grown from time to time from the beginning to date gradually as Home Science, Home Economic and developed as one of the primary job oriented subject. The Home Economic plays an important part in making students to reach high standard and transform them as good citizens. This research has it aims as to find the extend of dissemination of Home Economic students the problems faced in the course of teaching and learning and to recommend solutions for these problems. This research is designed as a research descriptive as it intends to describe and explain the problems faced in teaching and learing Home economic as a subject. 13 schools in Sandilipay Educational division teaching Home Economic as a subject are as model schools for the purpose of this research. Data obtained from 211 students, 11 teachers, Asst. Director of education, teacher’s advisors, principals and students through interviews observations. Subject analysis and questionnaires. As the state of dissemination of Home Economic students are considered a very few students opt to select Home Economic as a subject for his studies. The general opinion that this is a hard subject and the thought of getting poor result the negative mental attitude shown against this subject by large section of the society place restraints on students from selecting this subject. Finally many problems encountered in teaching and learning of Home Economic as a subject was identified shortage in resources has been found. It has been observed that tools and equipment’s for teaching. Learning was used property and efficiently in schools selected for this research. Many developments projects have been introduced for the development of Home Economic subjects by the education zone hewer it has been noted that these development activities have not been properly handled in some schools. These development projects are carried out only in certain particular schools. Teaching and learning of Home Economies can be further developed by more activities and by eliminating the shortages in the resources to recommend proposals to find solutions for three problems. When considering the state of extent and popularly of Home Economy it is necessary to mention that only very few students opt to select this subject and study It can be suggested that giving awareness via teachers, encourage class management, make preference on Home Economics learning, teachers and students using of development activities in a proper way and obtaining the resources needed for learning as successive ways for teaching and learning in Home Economics
Keywords: Home economics; Secondary school; Problems; Teaching & learning; Resources